Equine chorionic gonadotropin increases estradiol levels in the bovine oviduct and drives the transcription of genes related to fertilization in superstimulated cows - Fontes, Patricia K. [UNESP]; Razza, Eduardo M. [UNESP]; Pupulim, Antonio G. R.; Barros, Ciro M. [UNESP]; Souza Castilho, Anthony C. de (Wiley-Blackwell, 2019)
In the bovine oviduct, estradiol (E2) stimulates secretion and cell proliferation, whereas progesterone (P4) suppresses them. In this study, we have evaluated the effect of two superstimulatory protocols (follicle-stimulating hormone [FSH] or FSH combined with equine chorionic gonadotropin [eCG]) on the oviductal levels of E2 and P4 and its outcome on oviductal cells. Compared with the control group (a single pre-ovulatory follicle), we have observed that the cows submitted to FSH/eCG treatment showed a higher concentration of E2 in the oviduct tissue, together with a higher abundance of messenger RNA encoding steroid receptors (ESR1 and progesterone receptor), and genes linked to gamete interactions and regulation of polyspermy (oviduct-specific glycoprotein 1, heat-shock protein family A member 5, alpha-l-fucosidase 1 [FUCA1], and FUCA2) in the infundibulum and ampulla segments of the oviduct. However, we did not observe any modulation of gene expression in the isthmus segment. Even though the FSH protocol upregulated some of the genes analyzed, we may infer that the steady effect of FSH combined with eCG on oviduct regulation might benefit fertilization and may potentially increase pregnancy rates.
Keywords: cattle; female reproductive tract; gametes; gene expression; steroids; superovulation